Demo:Assessing Sports Related Concussion in Soccer Players Using Immersive VR Soccer - Raikwar, Aditya; Stephens, Jaclyn; Ortega, Francisco R. (2020 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2020)
Virtual Reality is gaining popularity due to the gaming industry. But there are many other applications of VR like training, rehabilitation, and simulation. This is our effort to combine all these application to create a technique for assessing return-to-play readiness in athletes with concussions using Virtual Reality (VR). The subjects perform various Soccer related simulations. By measuring their responses during the execution of these tasks we can asses their ability to return to the game.